2021
DOI: 10.1021/acsanm.1c01588
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Abundant and pH/NIR Dual-Responsive Nanocarriers for Tumor Hypoxia Reduction Therapy

Abstract: Pre-existing tumor hypoxia and oxygen consumption by photodynamic therapy (PDT) always generate an inadequate oxygen supply, which often contributes to other therapy resistance, especially for aerobic treatments such as chemotherapy. In order to overcome this problem, we synthesized a chitosan (CS)-capped pH-/NIR-dual responsive and perfluorocarbon-based oxygen self-enriching photodynamic therapy nanosystem which could codeliver oxygen, photosensitizer, and chemotherapeutic drug. Simultaneously, in vitro resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As detailed above, the TME represents palpable hypoxia, which poses a formidable challenge to cancer therapeutics. 66 In response to this, hypoxia-mediated controlled drug release systems have emerged in recent years and are being studied as a potential novel stimuli-responsive mechanism. 31 The hypoxia-responsive controlled release system depends on the hypoxia-triggered chemical bond rupture and alterations in the hydrophobicity of polymer materials.…”
Section: Chemotherapy Combined With Starvation Therapymentioning
confidence: 99%
“…As detailed above, the TME represents palpable hypoxia, which poses a formidable challenge to cancer therapeutics. 66 In response to this, hypoxia-mediated controlled drug release systems have emerged in recent years and are being studied as a potential novel stimuli-responsive mechanism. 31 The hypoxia-responsive controlled release system depends on the hypoxia-triggered chemical bond rupture and alterations in the hydrophobicity of polymer materials.…”
Section: Chemotherapy Combined With Starvation Therapymentioning
confidence: 99%
“…Although it is a way to combat hypoxia-induced resistance to oxygen delivered to tumor tissues, the oxygen supplement also offers more vitality to tumor cells. Thus, the solutions to hypoxia-induced resistance are the general need for synergetic therapy (Zhuang et al., 2021 ). Hypoxia counts against body cell mitosis as well as tumor cells, but hypoxia could promote epithelial-mesenchymal transition (EMT) which can accelerate tumor metastasis.…”
Section: Disrupting Energy Metabolism or Signal Pathwaysmentioning
confidence: 99%
“…The mechanisms of photosensitizer generating ROS can be divided two types: (1) Photosensitizer transfers light energy to either tissue substrate and produce superoxide anion radicals (such as O 2 − and HO 2 ), which is called as Type I reaction; (2) Photosensitizer directly converts O 2 molecules into singlet oxygen ( 1 O 2 ), which is Type II reaction (Aniogo et al., 2019 ). The ROS productions don’t only destroys tumor tissues but also decreases the HIF-1α expression (Pramual et al., 2020 ; Zhuang et al., 2021 ). Excessive ROS generated by photosensitizer could induce biomembrane lipid peroxidation and kill of cancer cells.…”
Section: Phototherapymentioning
confidence: 99%
“…Photodynamic therapy (PDT) relies on photosensitizers (PSs) to transfer energy to dissolved oxygen (O 2 ) within tumors, resulting in the generation of cytotoxic 1 O 2 for the treatment of cancer. Capitalizing on the ability of photodynamics to generate reactive oxygen, Wang et al reported the singlet oxygen-responsive features and corresponding reaction mechanism of a nitroimidazole-containing micelle . Gao et al encapsulated Ce6 with unsaturated fatty acids into polymer micelles, the singlet oxygen produced by Ce6 induces lipid peroxidation, leading to the generation of reactive free radicals and aldehydes .…”
Section: Introductionmentioning
confidence: 99%